2013
DOI: 10.4067/s0718-40262013000500003
|View full text |Cite
|
Sign up to set email alerts
|

Productividad y calidad metodológica de artículos clínicos en cirugía oral y maxilofacial en Chile: Período 2001-2012

Abstract: Productivity and methodological quality of clinical articles in oral and maxillofacial surgery in Chile. Period 2001-2012Introduction: Until now, there are no reports of quantity and quality of publications in oral and maxillofacial surgery (OMFS) conducted in Chile, which is why the aim of this study is to determine the productivity and methodological quality (MQ) of OMFS clinical articles in Chile in the period 2001-2012. Material and Methods: Bibliometric study. A systematic search in MEDLINE, Science Citat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 25 publications
1
12
0
5
Order By: Relevance
“…Unfortunately, in dentistry 4,5,8 and other biomedical sciences, 6 many published research articles would be considered to have a low LoE. However, LoEs provide an incomplete picture since studies that have the same LoE nominally, may differ in essential methodological aspects (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, in dentistry 4,5,8 and other biomedical sciences, 6 many published research articles would be considered to have a low LoE. However, LoEs provide an incomplete picture since studies that have the same LoE nominally, may differ in essential methodological aspects (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,8 An additional advantage of the MINCIR scale is that it enables one to perform systematic reviews of clinical trials, cohort studies, case-control, and case series studies. 11 The MINCIR scale has been used to assess surgical studies, 6 including studies in the areas of oral and maxillofacial surgery, 8 and has demonstrated psychometric properties. 12 However, these may vary depending on the study population; so it is necessary to have validation procedures to assure adequacy.…”
Section: Discussionmentioning
confidence: 99%
“…After the publication of the first version of the instructions for use of the MInCir scale to assess MQ of therapy studies , and its use in many bibliometric studies and SR (Manterola et al, 2003(Manterola et al, , 2005a(Manterola et al, , 2005b(Manterola et al, , 2006(Manterola et al, , 2009Claros et al;Arias et al;Moraga et al, 2013Moraga et al, , 2014Aravena et al;Santander et al;Cartes-Velasquez et al), the need to update its instructions became obvious. The main reason for this update is to adjust to the real situations in which the MQ of therapy studies are evaluated, in order to facilitate the allocation of scores for each of the items and domains.…”
Section: Discussionmentioning
confidence: 99%
“…The group MInCir developed and validated a scale to assess the MQ of studies on therapy or therapeutic procedures (Manterola et al, 2003;Manterola et al, 2006;Manterola et al, 2009;Moraga et al, 2013), which has been used to measure the MQ in surgical and dental areas (Aravena et al, 2013;Cartes-Velasquez et al, 2014). Similarly, this scale has been used for conducting systematic reviews (SR) with an alternative methodology (Arias et al, 2012;Claros et al, 2007;Manterola et al, 2005aManterola et al, , 2005bManterola et al, , 2007Moraga et al, 2014;Santander et al, 2013), allowing for the use of primary studies with different designs and evidence levels, thus overcoming the limitation of traditional methodology that only uses clinical trials (CT) as primary sources .…”
Section: Introductionmentioning
confidence: 99%
“…One of the scales that measures the methodological quality of CT is the MINCIR (Methodology and Research in Surgery) scale, which has demonstrated its validity 9 and reliability 11 and proven its use in the bibliometric analysis of articles in dental therapy research 12 and oral-maxillofacial surgery 13 . Its use in pediatric dentistry would make it possible to quantify the methodological quantity and quality of CT, minimizing the chances of error in the determination of the quality of the scientific literature 14 and contributing to the most current quantification of the evidence obtained in this specialty.…”
Section: Introductionmentioning
confidence: 99%